Pengaruh Substitusi Tepung Biji Nangka (Artocarpus Heterophyllus) Dan Labu Kuning (Cucurbita Moschata Durch.) Terhadap Sifat Organoleptik Cookies - Eusu Kirang; Asmulyati S Saleh; Maria F Vinsensia D P Kewa Niron (Kupang Journal of Food and Nutrition Research, 2026)
The prevalence of anemia is 32%, meaning that 3 to 4 out of every 10 adolescents have anemia. One way to address anemia is through the consumption of foods rich in iron and vitamin C. Jackfruit seeds and pumpkin are local food ingredients that contain iron, protein, and vitamin C, and can be processed into functional food products such as cookies. This study aimed to determine the effect of substituting jackfruit seed flour and pumpkin flour on the organoleptic properties and nutritional value of cookies as an effort to diversify nutritious local foods to prevent anemia in adolescent girls. This research was an experimental study using a Completely Randomized Design (CRD) with three treatments of jackfruit seed flour and pumpkin flour ratios: P1 (20%:25%), P2 (25%:20%), and P3 (30%:15%). Organoleptic tests were conducted by 30 student panelists from the Nutrition Department of Poltekkes Kemenkes Kupang. Data were analyzed using ANOVA to examine differences between treatments. Results: Conversion results showed that 1,000 grams of jackfruit seeds produced 650 grams of flour (conversion ratio 1.53:1), while 1,500 grams of pumpkin produced 400 grams of flour (conversion ratio 3.75:1). The organoleptic test results indicated that all treatments received average scores close to 5, categorized as “liked very much.” Treatment P3 (30%:15%) received the highest scores for color (4.90), aroma (4.73), texture (4.80), and taste (4.73). ANOVA results showed no significant differences (p>0.05) in all organoleptic aspects. Based on nutritional analysis, cookies from P1 (20%:25%) had the highest nutritional content, with protein 0.66 g, iron 0.17 mg, and vitamin C 0.36 IU per piece. To meet 10% of the daily iron requirement for adolescent girls, it is recommended to consume 11 pieces of P1 cookies. Conclusion: Substitution of jackfruit seed flour and pumpkin flour up to 45% (P3) produced cookies with a high level of preference without reducing organoleptic quality. P1 cookies are recommended because they have higher nutritional content, especially iron, protein, and vitamin C, which are beneficial in helping prevent anemia in adolescent girls.